Adapting industrial policies to a digital world for economic diversification and structrual transformation (UN New YorkUS, 2018)
Discusses how the diffusion of digital technologies shifts the traditional boundaries between individual industries and those between industry and services, and how this affects economic diversification and structural transformation.
Keywords: INDUSTRIAL POLICY